Pengaruh Penambahan Probiotik Starbio Dalam Ransum Terhadap Bobot Potong, Persentase Karkas Dan Persentase Lemak Abdominal Ayam Broiler. - Achmad Jaelani; Aam Gunawan; Syahid Syaifuddin (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
The aim of This research is to know the effect of added probiotic Starbio on ration to dressed percentage and abdominal lipid percentage of broiler chicken. This research was used Completely Randomized Design. The treatments are consists five dosage of Probiotic Starbio in ration ie: 0 g.kg-1 (control), 1,5 g. kg-1, 2,5 g. kg-1, 3,5 g. kg-1, dan 4,5 g. kg-1. Every treatment using four replications. Parameter were used in this research are slaughtered weight, dressed percentage, and abdominal lipid percentage. Data were analyzed by Anova and Duncan Multiple Range Test (DMRT) if refers difference significantly between treatments.The Result of this research showed that added of Probiotic Starbio in ration significantly different to slaughtered weight, dressed percentage and abdominal lipid percentage of broiler chicken commercial ration. Added Probiotic starbio on broiler chicken ration increase to slaughtered weight and dressed percentage but decrease to abdominal lipid percentage. This research was recomended that the using probiotic starbio till 4.5g.kg-1 in broiler chicken ration was to increased slaughtered weight (2.168,90 g), dressed percentage (75,10%) and decrease abdominal lipid percentage (2,55%)